Regression Model to Predict Production Rate Based on Market Demand in Medical Devices Manufacturing Company: Model Regresi Untuk Memprediksi Angka Produksi Berdasarkan Permintaan Pasar di Perusahaan Manufaktur Alat Kesehatan - Mulyadi, Akmad; Annisa, Zhudiah; Syahrorini, Syamsudduha (Universitas Muhammadiyah Sidoarjo, 2025)
This study aims to explore the use of regression models in predicting production figures at PT. Manufaktur Alkes Rumah Sakit, a company engaged in the manufacturing of medical devices, based on market demand. The purpose of this study is to understand the relationship between demand and production and to develop an accurate regression model. The results of the analysis show that every one unit increase in market demand can increase the average production figure by 0.803 units. This finding is expected to help management in planning production more effectively and responsively to market dynamics. In addition, this study recommends that further analysis be carried out by considering other variables to improve prediction accuracy.